2020
DOI: 10.21203/rs.3.rs-17950/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public Awareness And Knowledge Of Factors Associated With Myopia In Kisumu County, Western Kenya

Abstract: Background: Myopia is a global public health priority. Many modifiable and non modifiable risk factors have been shown to influence the development of myopia, but these factors are not adequately known by the general public. This study assessed public awareness of the factors that are associated with myopia among the general population in Kisumu County, Kenya. Methods: A cross-sectional study was conducted from October 2019 to February 2020 using an Internet-based questionnaire. We collected basic socio demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
3
1
0
Order By: Relevance
“…Considering the ease with which young people can access various information sources including social media and other internet-based platforms, it is not surprising that young people demonstrated better knowledge of myopia compared with the older people in this study. Similar to our findings, Muma and Oboyo [ 20 ] reported that younger age was significantly associated with knowledge of myopia risk factors and corrective measures [ 20 ]. Another study in Kenya found similar results indicating that myopia knowledge scores decreased with an increase in the age of the participants [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Considering the ease with which young people can access various information sources including social media and other internet-based platforms, it is not surprising that young people demonstrated better knowledge of myopia compared with the older people in this study. Similar to our findings, Muma and Oboyo [ 20 ] reported that younger age was significantly associated with knowledge of myopia risk factors and corrective measures [ 20 ]. Another study in Kenya found similar results indicating that myopia knowledge scores decreased with an increase in the age of the participants [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings, Muma and Oboyo [ 20 ] reported that younger age was significantly associated with knowledge of myopia risk factors and corrective measures [ 20 ]. Another study in Kenya found similar results indicating that myopia knowledge scores decreased with an increase in the age of the participants [ 20 ]. The current findings are in contrast with a KAP study from Ethiopia [ 28 ] which reported that awareness and knowledge of refractive errors increase with age.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations